The Effect of Compensation, Organizational Commitment on Employe Performance Through Organizational Behaviour as Intervening - Maria, Anna; Cen Pujianto, Jeanne Francoise (International Journal of Business, Law, and Education, 2024)
Performance is important for every organisation, including universities. Various factors influence performance, including compensation, organizational commitment (OC), and organizational behaviour (OB). These factors are the variables in this research. The aim of this research is to determine the effects of compensation and organizational commitment on employee performance through organizational behaviour as the intervention. This research is a quantitative research, using non-probability sampling and using a questionnaire for collecting the data. The research results show that compensation has a direct effect on Employee Performance (EP), Organizational Behavior (OB) has a direct effect on Employee Performance (EP), and Organizational Behavior (OB) can be a variable that links organizational commitment (OC) to Employee Performance (EP).